3G Handy Guide acting and TV presentation - 3G E-learning LLC; 3G E-learning LLC (New York, NY 3G E-learning LLC, 2020)
Acting, in its simplest form, is playing a role that is not your true character. Acting has been around for a long time, and art itself has a tendency to evolve over time. Artists have been breaking the traditional boundaries of what has been expected of them since Michelangelo and Picasso. The same is true of acting, so that performances can be achieved by different means because of the ever-changing cultural atmosphere. The acting profession has seen some positive developments in recent times. While many trained theater artists are trying to live off stage productions, the emerging Home Video Industry and private television stations provide opportunities for exhibitions of acting professionalism. In this guide, we will take a critical look at the essence of the act and its demands on the prospective performer. We will do this by analyzing the peculiarities of stage and screen acting. The essence of this is to create awareness that the medium has an impact on the approach. Unless the program is presented attractively, given the presentation techniques, good material and well written scripts will not have the desired impact. The presenters are members of the broadcasting company and serve as connections between the organiza-tion and the listeners. A successful presentation takes into account the aims of the show, the needs of the listener and a thorough understanding of the strengths and examples of the medium. A strong presentation addresses all the questions of the audience. Unlike television, only radio is heard in which neither the presenter nor the listener is visible. The presenter must create the illusion that he / she is with the listener, and that he / she is' talking' to him / her through voice, manner and style. Innovation, creativity, freshness and novelty are the main pillars on which the skill of presentation is built. The elements of rich vocabulary, information, knowledge and the ability to discern as to what to say and what not to say make these pillars strong and sturdy. An overall knowledge of broadcasting system stands the present-er in good stead. However, modernization, globalization and economic ambitions have contributed to a sea-change in their mindset, desires and demands.

This Handy Guide will cover television production processes right from selecting topic to the production of that programme. Along with TV acting students also learn required inputs on theories of performing Art, Classical Theater, Stage Craft and Lighting. Students also learn to handle Video Camera and work on basic Video Editing. Students will learn developing program briefs researching the topic, Program Resources, Style and format, structuring the program, Storyboard and Script Designing and Script Layout. Students prepare and physically for the rigorous year ahead. They learn to open up to the possibilities for acting by exploring core concepts, such as trust and play.

The Book comes with a companion DVD for rich learning experience, which includes: 1. E-Book with further readings and learning links. 2. Interactive e-lectures are expressive, informational, entertaining and persuasive, it uses the tool of self-exploration, which makes it easy to learn and understand each topic in detail. It is very informative as concrete details are provided and also entertaining, as graphics and other visuals are provided to make the learning process more interactive. 3. Video Lecture of each chapter, which explains each topic in detail with examples, animations, images, and text and makes it easy, simpler and better way 4. Huge Database of Interactive Assesment for each chapter, which is also printable 5. Further reading and learning links for each topic 6. Glossary and Notes for each chapter to understand each chapter with to the point information 7. The DVD also includes a printable workbook, which walks you through with a various sets of questions and choices and assists in completing the curriculum. The workbook covers; Learning Objectives, Essential Concepts, Matching Definitions, Study Problem, Questions, Fill in the Blanks and Answers

8. Review Questions for each chapter are also given in the DVD, which are also printable.

The DVD is also useful tool for teachers to teach with digital resources in classroom and do a great job of illustrating skills and techniques that are otherwise difficult to explain.
Includes bibliographic reference (page 237) and index (pages 239-240).
Keywords: Television broadcasting; Acting